Beyond The Classroom: StrengthsU - (:unkn) unknown (Kansas State University. K-State First., 2016)
A poster promoting the presentation “StrengthsU" at Kansas State University, hosted by Jessica Arnold, Assistant Coordinator of New Student Services, and Erin Poppe, StrengthsQuest Graduate Assistant, on February 2, 2016 at Derby Dining Center. The session includes discussion about students' personal strengths and engaged the students in two activities that reflected their strengths, as defined by the Gallup StrengthsQuest poll.
Keywords: Beyond The Classroom; Events; Engagement; Community building; Application of learning; StrengthsQuest; Posters